Procurement performance and supplier management measurement issues: A case of Malaysian private company - Nawi, M.N.M; Songappenm, M.; Nadarajan, Shanthi; Siti Halipah, Ibrahim; Mustapha, R. (ExcelingTech, 2017)
The rising material and operational cost for manufacturers in medical device industry is of concern to many organizations. As such, it is imperative to measure the procurement and supplier's performance for competitive advantage and provide a framework to stakeholders for continuous improvement. This paper develops a procurement and supplier performance measurement system at a firm by conducting a review of literature in procurement performance measurement and supplier performance measurement. Through the key components of supply chain together with the resources, procedures and output, a model was developed. Additionally, a system was established with a set of generic measures and six perspectives. The case study conducted at the firm applies to the model developed to describe the procurement department within the supply chain activities. Results indicate that supply chain department has already made a good progress in measuring procurement process through the implementation of supplier development program. Few areas that needed to be measured include cycle time of delivery, order processing time, effectiveness, efficiency and reliability. While a lot of hard work was involved, the advantages of establishing a measurement system outweigh the costs and efforts involved in its implementation. Results of key performance index measurements provide stakeholders with critical information on efficiency and effectiveness of the procurement department's work.